PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM ADVOKASI MASYARAKAT DESA PUTRAPINGGAN KECAMATAN KALIPUCANG KABUPATEN PANGANDARAN - Dadan Gunawan; Regi Refian Garis; Arie Budiawan (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
This research is motivated by a problem which shows that the Community Empowerment Institute has not played a role in advocating for the people of Putrapinggan Village, Kalipucang District, Pangandaran Regency. The purpose of this study was to determine the Role of Community Empowerment Institutions in Community Advocacy in Putrapinggan Village, Kalipucang District, Pangandaran Regency. The method used in this research is descriptive analysis. Informants as many as 8 people. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through data processing from interviews and observations to draw conclusions so that they can answer problems in research. Based on the research results it is known that: The role of Community Empowerment Institutions in community advocacy has not been carried out optimally according to the role of Community Empowerment Institutions, this can be seen from the inactivity of several LPM members in every village meeting, lack of interaction and socializing with all elements of society in the village, LPM members are less familiar and flexible in their interactions with the village community so they are less able to interact and attract the interest of the village community to participate in various activities carried out in the village, lack of sensitivity from LPM members to know the needs of the small business community in the village, lack of LPM has complete and accurate data regarding the need for infrastructure facilities for the benefit of the village community, lack of LPM members holding meetings with all elements of society in the village to listen to suggestions and input in physical development in the village and in community empowerment village aka.